Comparison of temporal and kinetic walking parameters among young people and falling and non-falling elderly persons - Ronaldo Valdir Briani; Bianca Taborda; Érica Caroline Carvalho Martines; Fernando Amâncio Aragão (Revista Brasileira de Geriatria e Gerontologia)
Objective : Comparison of the biomechanical parameters (spatiotemporal and kinetic) during walking of young people, falling, and non-falling elderly persons. Methods : A cross-sectional study was performed of 29 individuals divided into three groups: young persons (n=10); falling elderly individuals (n=7) and non-falling individuals (n=12). Gait analysis was performed based on the recording of three walking gait cycles along an 8 meter platform, which was attached to a force plate with a recording frequency of 200 Hz. Gait cycles were also recorded by three video cameras positioned perpendicular to the force plate with a recording frequency of 60 Hz. The data analyzed was: average step velocity, stance time, Froude number and anteroposterior ground reaction force. Results : The average step velocity was higher among young persons and there was no difference in the Froude number among the three groups. During the stance and impulse phase, anterior and posterior force was higher among young persons than in the non-falling elderly group. The foot stance time of young individuals was also lower than the non-falling elderly group (p=0.000) and the foot stance time of the falling elderly group was lower than that of the non-falling elderly group (p=0.004). Conclusion : Falling and non-falling elderly persons have different gait biomechanical characteristics than young women, other than with respect to the Froude number. Furthermore, falling elderly persons spend more time in the gait swing phase than non-falling elderly persons.